Age-Related Differences of Rumination on the Loneliness–Depression Relationship: Evidence From a Population-Representative Cohort. Issue 4 (29th August 2021) - Tong, Horace; Hou, Wai Kai; Liang, Li; Li, Tsz Wai; Liu, Huinan; Lee, Tatia M C
Abstract: Background and Objectives: This study examined the association of loneliness with depressive symptoms across various age groups. Loneliness is a significant risk factor for precipitating depressive symptoms. Rumination, a mechanism that underpins depression, can become intense when a person feels lonely. In addition, age is a major factor associated with changes in mental and physical health. Thus, the importance of rumination and age in moderating the loneliness–depression link were investigated. Research Design and Methods: This cross-sectional study was conducted during the acute phase of the coronavirus disease 2019 pandemic in Hong Kong (February 27 to March 17, 2020). A population-representative sample of 1, 972 people (1, 107 females; 18–92 years of age) was recruited and interviewed via telephone through random digit dialing. This sample included 394 younger adults (18–30 years), 1, 106 middle-aged adults (31–64 years), and 472 older adults (65 years or above). Respondents reported depressive symptoms, subjective loneliness, state rumination, and sociodemographic factors. Results: Loneliness and rumination were positively associated with depressive symptoms, and they significantly interacted in predicting cognitive-affective symptoms. Further analysis of age showed that the interaction was significant only in middle-aged adults and older adults. Both rumination and age interacted with loneliness, respectively, in predicting cognitive-affective symptoms. Discussion and Implications: These findings indicate that the strength of the association between loneliness and the cognitive-affective symptoms of depression depends on rumination levels and age. An intervention to regulate rumination offers a feasible direction for health care and social care aimed at improving older adults' mental health.